Pembentukan Kompetensi Pedagogik dan Profesional Guru SD melalui Hybrid Learning pada Pendidikan Profesi Guru Dalam Jabatan - Alben Ambarita (Universitas Negeri Padang, 2019)
The purpose of this study is to describe and analyze teacher readiness, implementation, ability to overcome obstacles, and follow up to follow the hybrid learning activities of Elementary School Teacher Professional Education in Occupation in the formation of pedagogical and teacher professional competencies in Elementary School. The research method that used is qualitative phenomenology, with a case study design that is describing and analyzing hybrid learning activities in Professional Teacher Education in the Position of Elementary School Teachers in 2019. Data analysis refers to the theory of Miles and Huberman (1994) conducted interactively through a process: (1) data collection, (2) data reduction, (3) data display, and (4) conclusion drawing and verification (conclusion drawing and verification) conducted during and after data collection, based on data findings and verification. The results showed that participants in the Elementary School Teacher Professional Education (1) had administrative readiness and determined academic requirements, (2) were able to participate in online hybrid learning well, (3) could overcome online obstacles through collaboration with other participants, and (4) can follow up on the workshop activities at the Educational Workforce Educational Institution.